Microwave and THz characterization of dielectric properties of bulk glass-ceramic composites and ULTCC substrates - Olszewska-Placha, Marzena; Varghese, Jobin; Synkiewicz-Musialska, Beata (Microwaves, Radar and Wireless Communications, International Conference on, 2024)
In this work, new ultra-low temperature co-fired glass-ceramic composite intended to serve as a dielectric substrate for microwave and millimeter wave applications is investigated. The new material is subject to characterization of dielectric properties in a wide frequency spectrum using resonant methods and time domain spectroscopy. The presented measurement methodology involving different measurement techniques and frequency ranges allows for comprehensive characterization of new ceramic materials at consecutive development stages, supporting optimization of a fabrication process. Dielectric constant (loss tangent) of the newly developed ULTCC substrate, which is intended to be lower than 15(0.01), creates a perspective for its future application as dielectric substrates for electronic systems.